(untitled) (Research, Society and Development, 2021)
This paper discuss psilocybin’s effect on the human organism and its therapeutic potential as a main or adjuvant medication for certain psychiatric diseases, more specifically, depression and anxiety, such as found in palliative care patients which are facing the end-of-life process, but also on those patients in which the conventional treatment was not effective. Recent studies also present the possibility of the use of psilocybin in the treatment of long-term psychiatric consequences of COVID. The available literature indicates that psilocybin promotes heightening of quality of life, modifications in the perception of self, perception of wholeness with the environment and spiritual experiences, which have great importante in the aforementioned groups of patients. Besides, it shows little to no side effects. This paper presents a review to reinforce the hypothesis of the therapeutic use of psilocybin in depression and anxiety in populations that can benefit the most of psychedelic therapy.